정량 분석을 통해 살펴본 산업공학 전공의 현황 - 전홍배; 신기태; 정슬기 (대한산업공학회지, 2022)
In this study, the current status of industrial engineering major is identified through quantitative data analysis to prepare for the fourth industrial revolution and a sharp drop in the school-age population. We have conducted a comparative analysis of industrial engineering with other majors in terms of various indicators related to students, graduates, and research. In addition, we have compared industrial engineering departments by the region and establishment type of universities.
Keywords: ndustrial Engineering; Quantitative Analysis; Analysis of Current Status